Definition of a mathematical function for analysis of a model for distribution of substratum in biocatalytic membrane - Krylovas, Aleksandras; Kulys, Juozas (Lietuvos matematikos rinkinys, 2007)
Mathematical model for distribution of substratum in biocatalytic membrane described by second order nonlinear differential equation, which solution is presented as a special mathematical function. In the paper authors construct asymptotical approximations of the function for small and big concentration of substratum.